Ciclos econômicos, expectativas e inflação: uma análise a partir de estimações da curva de Phillips Novo Keynesiana - Oliveira, Maria Thalita Arruda (2014)
This work analyzes the recent dynamics of Brazilian inflation expectations considering different environments to observe how a possible discretionary behavior of the monetary authority can interfere with forward-looking expectations of agents and how this interference can act on the response of inflation to fluctuations in economic cycles and the backward-looking and forward-looking expectations of agents in the NKPC framework. To do this, estimates of GMM-HAC and the NKPC, as well as its hybrid version, are used. The results suggest that in an environment of greate run certainty, inflation is shown to be much more sensitive to swings in economic cycles, as well as it shows an increase in its inertial component.